Sistem Pendukung Keputusan Dalam Menentukan Siswa Berprestasi Menggunakan Metode Simple Additive Weighting (Studi Kasus: MA Sahid) - Nurul Kamilah; Adhitya Nurachman, Muhammad; Dewi Primasari (Jurnal PROCESSOR, 2024)
Madrasah Aliyah Sahid always holds a selection of outstanding students every semester. The selection of exceptional students is carried out per class by determining the highest score from rank 1 to 3. However, the assessment of outstanding students is still based only on report card scores, so other aspects besides report card scores are not considered as criteria for exceptional students. This raises various problems such as students who have good report card scores but have shortcomings in several other aspects, which means that the selected outstanding students do not reach the required standards and do not get the best candidates. In dealing with this problem, a decision support system is needed to determine outstanding students using the SAW method. This method can produce the best data because it is done by finding the criteria and weight values ​​of each attribute, which is expected to help the school in carrying out the process of assessing outstanding students so that the results obtained are more effective and efficient. These criteria include violation points, achievement points, attendance, and attitudes and behavior. After the criteria are determined, a decision support system is created to determine outstanding students. The system development uses Waterfall which consists of needs analysis, system design, implementation, testing, and improvement process. The results of the system design are in the form of criteria and weight calculations to produce a decision matrix, a normalized matrix, and the results of the calculations in the SAW method.